Trauma Unit volumes: Is there a relationship with weather, sporting events and week/month-end times? An audit at an urban tertiary trauma unit in Cape Town - Milford, Karen (Department of Surgery, 2017)
Background: The Trauma Unit at Groote Schuur Hospital is a mature, tertiary, high-volume trauma referral centre. The number of patients being treated in the unit at any given time can vary greatly. There is evidence to suggest that these fluctuations may be related to external and environmental factors, such as time of the day, week and month, local weather and significant home-team sport matches. Objective: The objective of this audit was to determine the relationship between volumes of patients in the unit, and environmental factors. Specifically, we aimed to determine whether the numbers of patients presenting after motor vehicle collisions and interpersonal violence was related in any way to temporal factors (time of day, week and month), weather variables (temperature and precipitation), and whether or not major or home-team soccer matches were being played. Methods: Trauma Unit admission records were examined retrospectively, and the numbers of patients presenting to the unit per shift for a total of 17 months was recorded. Patients were grouped according to their presenting complaints. Weather data, Premier Soccer League and Bafana Bafana match locations and results, and information regarding public holidays and long weekends were obtained for the relevant shifts. Average daily attendances for interpersonal violence (IPV)-related injuries and motor vehicle collisions (MVCs) were compared across the various external factors described. Poisson regression models were fitted using Stata 13 (StataCorp. 2013. Stata Statistical Software: Release 13. College Station, TX: StataCorp LP). and used to express the relative incidence of attendances. These results were expressed using incidence rate ratios (IRRs). Results: In total, 16 706 attendances were recorded over 1 074 shifts. Of these, 7 350 (44%) attendances were due to injuries sustained as a result of interpersonal violence (IPV), and 3 188 (19%) were due to MVCs. Predictors of increased attendances due to MVC-related injuries were week day shifts, and night shifts on long weekends, and on weekends that fell on the last day of the month. Weekend nights shifts were busier than week night shifts from this perspective. Public holiday shifts were shown to have less MVC-related attendances than an ordinary week day. The presence of precipitation was also shown to increase the number of MVC-related attendances. IPV-related attendances were always increased on night shifts compared to day shifts, except on public holidays, long weekends, and on weekends that fell on the last day of the month. All weekend shifts were busier than their corresponding week day shifts from an IPV-related perspective, and this effect was enhanced on weekends that fell on the last day of the month. Long weekends showed very similar trends to ordinary weekends, and public holidays showed similar trends to ordinary week days. Increasing temperatures are associated with increased attendances due to IPV. Soccer matches and their outcomes have no significant effect on attendances due to IPV. Conclusions: Temporal and weather factors can be used to predict which trauma unit shifts will be busiest.